2004
DOI: 10.1159/000082865
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Bypass Procedures in Diabetic Patients with End-Stage Renal Disease: Is It Worthwhile?

Abstract: Backgroud/Aims: Limb-threatening ischemia in patients with end-stage renal disease (ESRD) represents a challenging therapeutic problem. Furthermore, diabetes mellitus is frequently associated with ischemic gangrene, persistent infection and impaired wound healing. The present study was undertaken to examine graft patency, limb salvage and survival in patients with ESRD and diabetes following bypass grafting to treat lower limb critical ischemia. Methods: A retrospective analysis of 56 arterial reconstructions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…[83] Another group performed infra-inguinal or axillofemoral bypass surgery in diabetic patients with ESRD. [84] Survival was 63% at one year and 45% at two years, while limb salvage rate was 65% at one year. Primary graft patency rates were 64% at one year and 58% at three years.…”
Section: The Diabetic Foot In Renal Failure: Prevention and Treatmentmentioning
confidence: 94%
See 1 more Smart Citation
“…[83] Another group performed infra-inguinal or axillofemoral bypass surgery in diabetic patients with ESRD. [84] Survival was 63% at one year and 45% at two years, while limb salvage rate was 65% at one year. Primary graft patency rates were 64% at one year and 58% at three years.…”
Section: The Diabetic Foot In Renal Failure: Prevention and Treatmentmentioning
confidence: 94%
“…Primary graft patency rates were 64% at one year and 58% at three years. [84] Improved limb salvage and patient survival rates, as well as reduced time to heal, have been accomplished by appropriate revascularization (angioplasty, femoro-popliteal, femoral-distal, popliteal-distal bypass surgery). [85] The department of vascular surgery at Beth Israel Deaconess Medical Center in Boston has reported primary graft patency rates of 84% and 64% at one and three years, respectively.…”
Section: The Diabetic Foot In Renal Failure: Prevention and Treatmentmentioning
confidence: 99%
“…7) According to other reports, also, the survival rate was low in patients on hemodialysis, but the graft patency rate was not inferior, and the results of bypass surgery for limb salvage were reasonable, encouraging aggressive revascularization. [8][9][10][11][12] In patients with DM and those undergoing HD, the obstructive lesion is often located in a lower leg artery and is accompanied by marked calcification. Therefore, a sufficient blood supply to the foot by dorsalis pedis, posterior tibial, or plantar artery bypass surgery using a venous graft, which is obtained primarily from the greater saphenous vein, is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…While some investigators have found that bypass surgery may be beneficial to this patient population, others could not support this finding. Georgopoulos et al [1] have found that the limb salvage rate in patients with ESRD and diabetes justifies limb revascularization, despite the decreased survival of this population. Treiman et al [2] stated that patients with impaired renal function are at increased risk for treatment failure due to potential impaired wound healing, but they nonetheless should not be denied revascularization surgeries, since the wounds may successfully heal.…”
Section: Zusammenfassung Einfluss Der Femoropoplitealen Bypassoperatimentioning
confidence: 99%